BS EN 3488. Aerospace series. Steel X6CrNiTi18-10 (1.4541). Air melted. Softened. Sheets and strips. a ≤ 6 mm. 500 MPa ≤ Rm ≤ 700 MPa. (17th September 2020) - British Standards Institution,
No abstract available